False echocardiographic diagnosis of aortic root dissection in case of abdominal aortic dissection. - Kolettis, M (1981)
A patient with strong clinical and radiological indications of dissection involving the ascending aorta had this "confirmed" on an echocardiogram which showed a typical pattern of double lumen. At necropsy there was dissection of the abdominal aorta but the heavily calcified thoracic aorta was free of dissection. Echocardiography may be useful but not entirely reliable in the diagnosis of dissection even in the presence of a typical clinical picture.